THE STATUS OF ARGUMENTS IN ABSTRACT ARGUMENTATION FRAMEWORKS. A TABLEAUX METHOD - GUSTAVO A. BODANZA; ENRIQUE HERNÁNDEZ-MANFREDINI (Manuscrito, 2023)
Abstract Dung’s argumentation frameworks are formalisms widely used to model interaction among arguments. Although their study has been profusely developed in the field of Artificial Intelligence, it is not common to see its treatment among those less connected to computer science within the logical-philosophical community. In this paper we propose to bring to that audience a proof-theory for argument justification based on tableaux, very similar to those the Logic students are familiar with. The tableaux enable to calculate whether an argument or subset of arguments are accepted or rejected in accordance to Dung’s preferred and grounded extension-based semantics. Soundness and completeness results regarding those semantics are provided.